Hard Skills and Soft Skills on Performance: Influence and Application of Bengkulu City Education Service Employees - Daniel Lukito (East Asian Journal of Multidisciplinary Research, 2023)
Improving performance is something that is desired, both from the employer and the workers, so hard skills and soft skills are needed that are competent in employee behavior and performance skills. The purpose of this study is to ascertain how employees of the Bengkulu City Education Department perform in relation to hard and soft skills. This study employs quantitative methods. This study employed a questionnaire method using 102 Bengkulu City Education Office employees who had attained the ASN status as a sample. According to the results, the multiple linear regression Y = 19.309 + 0.295 (X1) + 0.360 (X2) + 1.053 shows a positive or unidirectional relationship between the hard skills (X1) and soft skills (X2) variables and employee performance (Y) at the City Education Office Bengkulu. The results of the t test indicate that employee performance (Y) in the Bengkulu City Education Office is positively and significantly impacted by the hard skill variable (X1). Additionally, the soft skill variable (X2) has a tcount value of 8.231> ttable 1.984 and a significance of 0.000 <0.05.  These findings bolster the acceptance of hypothesis Ha and the rejection of hypothesis Ho. The soft skill variable (X2) had a positive and significant impact on employee performance (Y) at the Bengkulu City Education Office, according to the results of the t test, which revealed a tcount value of 8.231> ttable 1.984 and a significance of 0.000 <0.05.